Studi Klitika dalam Bahasa Banjar Hulu Kabupaten Indragiri Hilir - Rasdana, Oki; Asnawi, Asnawi (GERAM: Gerakan Aktif Menulis, 2023)
The purpose of this study is to describe clitics in the Banjar Hulu language as an important element of the Malay language. The research method used is qualitative, and data collection techniques include listening, tapping, and analysis based on Miles and Huberman's data analysis techniques. The results reveal the presence of 19 clitics in the Upper Banjar language, which are: 1) ai, 2) pang, 3) bahai, 4) ni?, 5) tu?, 6) heh, 7) leh, 8) lah, 9) kah, 10) pound, 11) nang, 12) no, 13) nya?, 14) gen, 15) neh, 16) zinc, 17) ku?, 18) you?, and 19) ha?, in both proclitic and enclitic forms. Among these clitics, three can function as both proclitics and enclitics. The identified meanings of the clitics include annoyance, affirmation, adverbs, doubts, inventions, distrust, astonishment, serving as auxiliary verbs, pronouns, adverbs, and clothing-related words. This research demonstrates that the Upper Banjar language has a greater number of clitics compared to Indonesian and English.